Fusing pollen-stratigraphic and dendroclimatic proxy data to reconstruct summer temperature variability during the past 7.5 ka in subarctic Fennoscandia - Helama, Samuli; Seppä, H.; Bjune, A.E.; Birks, H.J.B. (Journal of Paleolimnology)
1